An 8‐item short form of the Eating Disorder Examination‐Questionnaire adapted for children (ChEDE‐Q8). Issue 6 (25th January 2017) - Kliem, Sören; Schmidt, Ricarda; Vogel, Mandy; Hiemisch, Andreas; Kiess, Wieland; Hilbert, Anja
Abstract: Eating disturbances are common in children placing a vulnerable group of them at risk for full‐syndrome eating disorders and adverse health outcomes. To provide a valid self‐report assessment of eating disorder psychopathology in children, a short form of the child version of the Eating Disorder Examination ( ChEDE‐Q ) was psychometrically evaluated. Similar to the EDE‐Q, the ChEDE‐Q provides assessment of eating disorder psychopathology related to anorexia nervosa, bulimia nervosa, and binge‐eating disorder; however, the ChEDE‐Q does not assess symptoms of avoidant/restrictive food intake disorder, pica, or rumination disorder. In 1, 836 participants ages 7 to 18 years, recruited from two independent population‐based samples, the factor structure of the recently established 8‐item short form EDE‐Q8 for adults was examined, including measurement invariance analyses on age, gender, and weight status derived from objectively measured weight and height. For convergent validity, the ChEDE‐Q global score, body esteem scale, strengths and difficulties questionnaire, and sociodemographic characteristics were used. Item characteristics and age‐ and gender‐specific norms were calculated. Confirmatory factor analysis revealed good model fit for the 8‐item ChEDE‐Q . Measurement invariance analyses indicated strict invariance for all analyzed subgroups. Convergent validity was provided through associations with well‐established questionnaires and age, gender, and weight status, in expected directions. The newly developed ChEDE‐Q8 proved to be a psychometrically sound and economical self‐report assessment tool of eating disorder psychopathology in children. Further validation studies are needed, particularly concerning discriminant and predictive validity.